Sistem pendukung keputusan menggunakan metode analytical hierarchy process (ahp) dalam penentuan kualitas bibit cabai - DWI JULISA UTARI; Gunadi Widi Nurcahyo; Yuhandri Yunus (Universitas Muhammadiyah Riau, 2023)
The system is a network of procedures made according to an integrated pattern to carry out the main activities of a company in which there is an information system which is interconnected with one another which ultimately produces information/data that is useful for the intended person according to its designation. Today's Decision Support Systems (DSS) have assisted an organization in helping make important decisions in various sectors. One of them is the agricultural sector. Chili is a horticultural crop that is widely grown by farmers and the community, one of these plants is used as an ingredient for cooking. The purpose of this research is to provide convenience in determining the quality of chili seeds to farmers and the community. The data processed in this study were 5 criteria and 6 alternatives. Data on the quality of chili seeds obtained from the TPHP Office of Sungai Penuh City. The data is processed first, calculated manually and followed by applying calculations from the Analytical Hierarchy Process method. The processing steps determine the weight of each criterion, assign a score (paired comparison), summarize all scores (total weight). During data processing, the level of accuracy is still calculated. The result of testing this method is that the calculation of chili seeds has an accuracy of 83% based on the quality level of the specified criteria. Specifically, the testing decision support system is able to identify the quality of chili seeds. The level of accuracy achieved by the analytical hierarchy process is quite accurate and can help farmers and the community.